2020
DOI: 10.3390/jcm9072286
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Targeted Biopsy Yield (LOFTY Study) in Ulcerative Colitis Surveillance Colonoscopy

Abstract: We previously performed a randomized controlled trial (RCT) comparing targeted and random biopsy in neoplasia detection in patients with ulcerative colitis (UC), which showed the short-term effectiveness of targeted biopsy with one-time colonoscopy. In this retrospective cohort study, we investigated the long-term effectiveness of targeted biopsy in tertiary care hospitals, using the follow-up data from patients with UC for ≥ 8 years who had enrolled in the initial RCT. The primary outcome was death from color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Subsequent studies confirmed the low yield of random biopsies [51,[56][57][58]. Interestingly, these findings were corroborated by the retrospective study of Hata et al, where HD-WLE with only targeted biopsies have proven to be as effective over the long-term as targeted plus random biopsies with no death from CRC in both groups with median 8.8-year follow-up [59]. In addition, a cost-effectiveness analysis by Konijeti et al found that DCE with targeted biopsies was more effective and less costly than WLE with random biopsies.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Subsequent studies confirmed the low yield of random biopsies [51,[56][57][58]. Interestingly, these findings were corroborated by the retrospective study of Hata et al, where HD-WLE with only targeted biopsies have proven to be as effective over the long-term as targeted plus random biopsies with no death from CRC in both groups with median 8.8-year follow-up [59]. In addition, a cost-effectiveness analysis by Konijeti et al found that DCE with targeted biopsies was more effective and less costly than WLE with random biopsies.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the authors concluded that surveillance with only targeted biopsies could emerge as a more cost-effective strategy [58]. These results were consolidated by a subsequent retrospective cohort study based on the follow-up data of this RCT demonstrating the long-term effectiveness of targeted biopsies [59]. Indeed, no death by CRC was observed in both arms with a median 8.8-year follow-up.…”
Section: Random Biopsies In the Era Of Hdmentioning
confidence: 78%
See 1 more Smart Citation
“…Prior studies have shown that dysplasia detection from targeted biopsies are similar to and preferred over random biopsies 13‐15 . Importantly, in a follow‐up study 29 that used data from patients with UC for ≥8 years who had enrolled in the initial RCT, 14 no patient died of CRC in either the targeted or the random biopsy group within a median follow‐up of 8.8 years, demonstrating a robustness for targeted biopsy in terms of preventing CRC‐related mortality. On the other hand, there are also emerging data that random biopsies during surveillance chromoendoscopy may be warranted in patients with a personal history of neoplasia, 30 a tubular appearing colon, 30 concomitant primary sclerosing cholangitis, 30,31 long disease duration 31 and those with active inflammation 31 .…”
Section: Discussionmentioning
confidence: 93%
“…[ 2 ] In addition, diagnosis of UC mainly relies on endoscopy and clinical symptoms. [ 3 ] It has been reported that the occurrence rate of UC is increasing globally. [ 4 ] Furthermore, the incidence of UC is increasing worldwide over the past few years, affecting mostly young individuals.…”
Section: Introductionmentioning
confidence: 99%